The molecular mechanism by which heat stress during the grain filling period inhibits maize grain filling and reduces yield - Li, Xiaohu; Zhuge, Shilin; Du, Jiyuan; Zhang, Peng; Wang, Xingyu; Liu, Tianjian; Li, Donghui; Ma, Haoran; Li, Xinzheng; Nie, Yongxin; Liao, Changjian; Ding, Haiping; et al. (Frontiers in Plant Science, 2025)
High temperatures significantly impair plant growth and development by restricting maize grain filling; however, the molecular mechanisms underlying heat stress remain poorly understood. In this study, 350 maize inbred lines were evaluated under field conditions, leading to the identification of heat-tolerant Zheng58 and heat-sensitive Qi319. The two inbred lines were exposed to controlled conditions of 30°C/20°C (optimal) and 42°C/30°C (heat stress) during the grain filling period. Heat stress significantly reduced thousand-kernel weight and seed setting rates, with Qi319 experiencing more pronounced declines. In contrast, Zheng58 showed superior performance, with a grain filling rate 48% higher and seed setting rate 57% greater than Qi319. Transcriptome analysis showed that heat stress disrupted starch biosynthesis and hormonal homeostasis, notably affecting abscisic acid and auxin pathways. Additionally, photosynthetic and transpiration rates in panicle leaves were reduced due to the downregulation of genes related to light-harvesting complexes, photosystem I subunits, and water transport. These findings highlight the critical roles of starch metabolism, hormonal regulation, and photosynthetic efficiency in heat tolerance, offering valuable insights for developing heat-resilient maize varieties to mitigate yield losses under high-temperature conditions.